2020
DOI: 10.3390/antiox9030194
|View full text |Cite
|
Sign up to set email alerts
|

Emodin Scavenging of Superoxide Radical Includes π–π Interaction. X-Ray Crystal Structure, Hydrodynamic Voltammetry and Theoretical Studies

Abstract: The naturally occurring anthraquinone emodin is found in many plants that have been part of traditional Chinese medicine (TCM) for thousands of years. Recent pharmacological studies suggest that emodin might be a valuable therapeutic option for the treatment of various diseases. We describe the antioxidant effects of emodin on the superoxide radical. Our techniques include X-ray crystallography, density functional theory (DFT), and a recently developed cyclovoltammetry improvement, the rotating ring-disk elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
2
16
1
Order By: Relevance
“…In fact, many fungal phytotoxins have other biological activities in addition to their phytotoxic activity. For example, emodin ( 86 ) exhibits antioxidant [ 342 ], antitumor [ 343 ], phytotoxic [ 86 ], insecticidal [ 344 ], antimicrobial [ 344 ], and acetylcholinesterase (AChE) and glutathione S -transferase (GST) inhibitory [ 344 ] activities. In addition, many other isolated fungal metabolites have not been evaluated for their phytotoxic activities due to either the lack of phytotoxic assays or not enough of the compounds could be isolated to perform toxicity assays.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In fact, many fungal phytotoxins have other biological activities in addition to their phytotoxic activity. For example, emodin ( 86 ) exhibits antioxidant [ 342 ], antitumor [ 343 ], phytotoxic [ 86 ], insecticidal [ 344 ], antimicrobial [ 344 ], and acetylcholinesterase (AChE) and glutathione S -transferase (GST) inhibitory [ 344 ] activities. In addition, many other isolated fungal metabolites have not been evaluated for their phytotoxic activities due to either the lack of phytotoxic assays or not enough of the compounds could be isolated to perform toxicity assays.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Emodin (1, 3, 8-trihydroxy-6-methylanthraquinone) is a natural anthraquinone derivative, and is the main ingredient of many herbs including rhubarb, polygonum multiflorum , and polygonum cuspidatum ( Dong et al., 2016 ; Monisha et al., 2016 ). Pharmacological studies have shown that emodin, as a polyvalent molecule, has a variety of biological functions, such as anti-inflammatory ( Li X. et al., 2020 ; Xu et al., 2020 ), anti-bacterial ( Ji et al., 2020 ), anti-cancer ( Wu C. et al., 2019 ; Ma et al., 2020 ; Rossi et al., 2020 ) and inhibition of oxidative stress( Lee et al., 2020 ). Emodin has also been shown to have potent anti-cardiovascular activities in vitro and in vivo , including anti-inflammatory ( Wu et al., 2007 ), antioxidant damage ( Du and Ko, 2005 ), inhibition of myocardial cell fibrosis ( Evans et al., 2020 ) and other pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently described the antioxidant activity of emodin, another quinone plant natural product [ 52 ]. Emodin and embelin possess similar redox properties, and their capture of an electron by the quinone ring are closely related [ 53 ].…”
Section: Resultsmentioning
confidence: 99%